Weed suppression and yield response of high-density cotton to herbicides and spray fluid volumes through drone spraying - Pon Arasan, A; Radhamani, S; Pazhanivelan, S; Kavitha, R; Raja, R; Kumaraperumal, R; Firnass, M M R A (Plant Science Today, 2025)
Drone application of herbicides is an emerging concept in weed management. For drone spraying, spray volume needs to be optimized to improve its efficacy. The present study was conducted at Tamil Nadu Agricultural University, Coimbatore, during summer, 2024 to optimize spray volumes for drone spraying of herbicides in high-density cotton. The study was designed in a strip-plot with 3 horizontal plots (herbicides: H1 - PE application of pendimethalin 1kg/ha followed by hand weeding at 25DAS, H2 - PE application of pendimethalin 1kg/ha followed by EPoE application of quizalafop-ethyl 50 g/ha + pyrithiobac-sodium 62.5 g/ha and H3 - EPoE application of quizalafop-ethyl 50 g/ha + pyrithiobac-sodium 62.5 g/ha), 5 vertical plots (spray volumes: S1 - 30 L/ha, S2 - 35 L/ha, S3 - 40 L/ha, S4 - 45 L/ha, S5 - 50 L/ha) and replicated thrice. A weed-free check and an unweeded check were maintained separately. Regarding herbicides, pendimethalin followed by quizalafop-ethyl + pyrithiobac-sodium and pendimethalin followed by hand weeding, recorded lower total weed density and dry weight and higher drymatter production of cotton and seed cotton yield. Application of herbicides with 45 L/ha and 50 L/ha recorded lower total weed density and dry weight, higher drymatter production of cotton and seed cotton yield. The results revealed that the drone spraying of pendimethalin 1.0 kg ha-1 as pre-emergence followed by EPoE application of quizalafop ethyl 50g/ha + pyrithiobac sodium 62.5 g/ha with spray volume of 45 L/ha was found to be effective in combating the weeds in high-density cotton.